2017
DOI: 10.4236/ijcm.2017.84022
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Infraclavicular Axillary Vein Cannulation

Abstract: Background and Objective: Percutaneous central venous cannulation is a common invasive procedure. In comparison with an external landmark technique, the advantages of ultrasound-guided venous access include direct visualization of the anatomy and in vivo visualization of venous cannulation. Methods: We evaluated an ultrasound-guided technique for infraclavicular axillary vein cannulation, focusing on its ease of use, success rate and complications rate. One hundred and twenty patients who submitted to central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The benefits of this venous route are evident. 2,8,9,15 Visualization is greater through ultrasound use and vessel position is on the thoracic cage, but without direct contact with the pleura, offering a potentially lesser risk of pneumothorax. There is now much published evidence recommending the routine use of dynamic, real-time ultrasound guidance to improve central venous cannulation successes and reduce iatrogenic complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of this venous route are evident. 2,8,9,15 Visualization is greater through ultrasound use and vessel position is on the thoracic cage, but without direct contact with the pleura, offering a potentially lesser risk of pneumothorax. There is now much published evidence recommending the routine use of dynamic, real-time ultrasound guidance to improve central venous cannulation successes and reduce iatrogenic complications.…”
Section: Discussionmentioning
confidence: 99%
“…As the location of AxVs confers a reduced risk of infection and improved visualization with ultrasound, it is increasingly suggested that AxV catheterization is not only a good alternative, but also provides several additional benefits. 9,14,15 The outcome of this prospective observational study is to determine the degree of dynamic variation of the AxV size prior to the induction of anesthesia and after commencing mechanical ventilation, highlighting changes in intrathoracic pressure that affect AxV size. These changes can potentially impact the process of placing a centrally inserted central catheter (CICC) in the AxV as well as in the development of latent complications after device placement.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of US guided CVC, the infraclavicular approach to the AV was rediscovered. Nowadays, the technique of US guided AV catheterization has been well described, [7][8][9] but the evidences for its efficacy and safety compared with landmark guided SCV cannulation have not been comprehensively appraised. Thus, we conducted a systematic review and meta-analysis of RCTs to assess the effectiveness and safety of US guided AV catheterization.…”
Section: Introductionmentioning
confidence: 99%
“…However, axillary vein catheterization is usually performed under ultrasound guidance because of the deep position of the axillary vein. [15][16][17][18][19] At present, two ultrasound-guided catheterization techniques are commonly used: the long-axis/in-plane approach and the short-axis/out-of-plane approach. The advantage of the short-axis/out-of-plane approach is that the artery and vein can be visualized simultaneously, but the drawback is that part of the vascular access needle cannot be visualized at the time of catheterization, especially the tip of the vascular access needle.…”
Section: Introductionmentioning
confidence: 99%